Answer:
The correct answer is -521.6 KJ/mol
Step-by-step explanation:
In order to solve the problem, we have to rearrange and to add the reactions with the aim to obtain the requested reaction.
We have:
1) H₂(g) + F₂ (g) → 2HF(g) => ∆H₁ = -546.6 kJ/mol
2) 2H₂(g) + O₂(g) → 2H₂0(l) => ∆H₂ = -571.6 kJ/mol
If we multiply reaction 1 by 2 and add the inverse reaction of 2, we obtain:
2H₂(g) + 2F₂ (g) → 4HF(g) => 4 x ∆H₁ = 4 x (-546.6 kJ/mol)
2H₂0(l) → 2H₂(g) + O₂(g) => (-1) x ∆H₂ = (-1) x (571.6 kJ/mol)
-------------------------------------
2H₂(g) + 2F₂ (g)+ 2H₂0(l) → 4HF(g) + 2H₂(g) + O₂(g)
We eliminate 2H₂(g) is repeated in both members of the reaction, and we obtain: 2F₂(g) + 2H₂0(l) -> 4HF(g) + O₂(g)
Finally, the ΔH of the reaction is calculated as follows:
ΔHtotal= (2 x ΔH₁) + ((-1)ΔH₂
ΔHtotal= (2 x (-546.6 KJ/mol)) + ((-1) x (-571.6 KJ/mol)
ΔHtotal= -521.6 KJ/mol